Effects of Thermal Treatment on the Physical Properties of Edible Calcium Alginate Gel Beads: Response Surface Methodological Approach - Kim, Seonghui (Foods, 2019)
Calcium alginate gel (CAG) has been widely investigated for the development of artificial foods; however, there are few studies on its thermal stability. This study aimed to monitor changes in the physical properties of CAG beads during heat treatment using response surface methodology. Heating temperature (X(1), 40–100 °C) and heating time (X(2), 5–60 min) were chosen as independent variables. The dependent variables were rupture strength (Y(1), kPa), size (Y(2), μm), and sphericity (Y(3), %). The heating temperature (X(1)) was the independent variable that had a significant effect on the rupture strength (Y(1)) and size (Y(2)). Rupture strength (Y(1)) increased as the heating temperature (X(1)) increased; at the same time, the CAG beads size (Y(2)) decreased. With all conditions, the values of sphericity (Y(3)) were over 94%. SEM images revealed that increase in the rupture strength of the CAG beads by heat treatment resulted from their porous structures. Loss of moisture by syneresis, occurring with heat treatment, was judged to create a dense porous structure of CAG beads. Our findings offer useful information for cooking or sterilizing food products utilizing CAG beads. In addition, thermal treatment could be applied to produce hard CAG beads with a high rupture strength.